Study on Manufacture of The Equipment for The Fabrication Of Carbon/Epoxy Prepreg Composites - Pham , Thanh Nhựt (Journal of Technical Education Science, 2018)
Advanced composite materials have been studied and applied widely in the world but still limited in Vietnam. One of the reasons for this problem is the high cost of a machine. Hence, the equipment for the manufacture of carbon/epoxy prepreg composites (CPME-1) was fabricated and tested. CPME-1 can be used for study and research in the universites of Vietnam. Design of CPME-1 was based on the operation principle of the Autoclave machine. The advantages of CPME-1 are safe, small and easy to use. Additionally, it’s low cost compared to the price of Autoclave (about 1/8 times). The tensile test and flexural test results of carbon/epoxy prepreg composites were made by CPME-1 show that these values received from 80% to 95% compared to standard values. Therefore, this equipment initially only meets the requirements for teaching and study of the composite material field.